Site productivity indices for native forests in southeast Queensland. Issue 1 (December 2021) - Jay, V A; Neumann, M
Abstract: Site productivity, or site quality, describes the potential biomass growth and yield of vegetation at a given location. Land managers have devised indices for site productivity using attributes related to plant yields or growth rates, and these have great utility when available spatially in maps. The main factors determining site productivity include climate, soil and terrain characteristics. Here we analysed four productivity indices (two based on remote sensing only, two based on modelling and algorithms using spatial datasets). The tested indices were available over a 150, 000 km 2 area of southeast Queensland Australia, a region dominated by Eucalyptus and Acacia species. We were interested in comparing the indices regarding underlying drivers, effects on vegetation types and the general distribution of site productivity across our study region. Our methods included histograms of spatial attribute intersection, and multivariate linear regression. Remote sensing has clear advantages in capturing current conditions, which potential productivity algorithms cannot depict. On the other hand, maps with productivity algorithms provide large-scale robust information on biomass growth/yield that is sensitive to the main drivers of plant growth (e.g. climate, soil).